2021
DOI: 10.1177/00469580211007264
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and Health Status Disparities Associated with Difficulty in ADLs and IADLs among Long-Lived Populations in Brazil: A Cross-Sectional Study

Abstract: Objective: To evaluate the association between socioeconomic factors, health status, and Functional Capacity (FC) in the oldest senior citizens in a metropolis and a poor rural region of Brazil. Method: Cross-sectional study of 417 seniors aged ≥80 years, data collected through Brazil’s Health, Well-being and Aging survey. FC assessed by self-reporting of difficulties in Activities of Daily Living (ADLs) and Instrumental Activities of Daily Living (IADLs). Chi-square tests and multiple logistic regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The odds of severe IADL disability were lower among urban elderly than their rural counterparts. Previous studies agree with this study in nding that rural elderly tend to have a higher risk of IADL disability than their urban counterparts [40,49]. Availability of better healthcare infrastructure in urban areas could be attributed to lower risk of IADL disability among urban elderly.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The odds of severe IADL disability were lower among urban elderly than their rural counterparts. Previous studies agree with this study in nding that rural elderly tend to have a higher risk of IADL disability than their urban counterparts [40,49]. Availability of better healthcare infrastructure in urban areas could be attributed to lower risk of IADL disability among urban elderly.…”
Section: Discussionsupporting
confidence: 90%
“…Availability of better healthcare infrastructure in urban areas could be attributed to lower risk of IADL disability among urban elderly. In rural areas, the elderly depend more on family members or other people to manage their nances, payments, and purchases and avoid traveling to carry out these functions, leading to severe IADL among them [49]. Studies have noted that the elderly in urban areas have better access to healthcare, availability of logistic support in transportation, and better nancial support in the form of retirement bene ts that keep them free from functional disabilities [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Moreover, a higher prevalence of difficulties in ADLs/IADLs has been reported in studies involving urban elderly people with financial constraints. 9 However, little is known about the association between depressive symptoms and ADL/IADL disabilities among community-dwelling older Chinese individuals from urban low-income families.…”
Section: Introductionmentioning
confidence: 99%
“…The association between disability and chronic diseases has been described in recent studies [ 8 , 47 ]. In a previous study with Brazilian longevous populations, it was shown that inadequate weight, stroke, and joint disease were independently associated with limitations for ADLs, while chronic diseases were associated with difficulties for IADLs in a rural community where there is little variability in socioeconomic conditions [ 48 ]. Multimorbidity should be considered as a possible confounding variable in the analyses, since they tend to be associated both with the outcomes and explanatory variables, being a limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%